Consumer Committees in Tensions? A Interpretive Case of Lalitpur Metropolitan City, Nepal - Adhikari, Devendra; Pasa, Rajan Binayek (Nepalese Journal of Development and Rural Studies, 2019)
The people of Nepal have witnessed several political/social transformations in the country, which have resulted in the restoration of peace, the promulgation of the new constitution. The restructuring of the country into 753 local units has led to the substantive devolution of the 22 power power/jurisdictions from the center to the local governments. In this scenario, the local governments implement their development plans through consumer committees by mobilizing the local beneficiaries. The purpose of this paper is to explore the difficulties faced by these novice committees in getting development funds from the local governments even in urban cities. The paper is based on a qualitative study with an interpretative case study design. The study has revealed that the chaos of bureaucratic hurdles to receive the development budgets from the Metropolitan office is demoralizing the community volunteers at local levels. Local government should facilitate the fund releasing process to the consumer committees by easing the rules and regulations. There must be a shared governance system between the local government and beneficiaries so that both parties feel a shared responsibility to achieve any development goals. Likewise, the government should have the lead governance towards the banking institutions. Banks are the mediators between the government and the consumer to make the fund-releasing process becomes swifter and less complicated. The findings of this study could be useful in framing appropriate plans/policies for the local governments, to encourage the community people to participate as volunteers in local development projects.